The Role of Cell Membranes in Cell Traffic - Rara Inggarsih; Amalia, Ella; Septi Purnamasari (HM Publisher, 2021)
The cell membrane plays an important role in cell traffic because it functions to secrete various molecules. The selective transport system allows the movement of molecules into or out of the cell compartment. By controlling the movement of substances from one compartment to another, membranes exert a strong influence on metabolic pathways. Cell membranes are composed of proteins and lipids with a very important function in maintaining the rhythm of circulation and cell transport. In addition, the cell membrane also plays a role in maintaining the integrity and relationship, and communication of cells.